Kepemimpinan Lembaga Pendidikan Islam Di Madrasah Tsanawiyah Hifzil Qur’an - Siahaan, Amiruddin; Nur’aini, Intan; Qatrunnada, Qatrunnada; Lbs, Erfiani; Pulungan, Farhan (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to find out the leadership of Islamic educational institutions in Madrasah Tsanawiyah Hifzil Qur'an. The approach of this research is qualitative research with a descriptive method. The informant in this study is the Deputy Head of Madrasah for Curriculum at Madrasah Tsanawiyah Hifzil Qur'an Medan who was selected using puposive sampling techniques. The data collection technique from this mini research is observation. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. Based on the results of the data analysis, it can be concluded that the heads of madrassas in Islamic educational institutions show democratic leadership traits such as attention, discipline, initiative, wisdom, openness, and stable emotions in their daily actions. There are five strategies used to encourage the performance of teachers and education personnel, namely (1) involving education personnel (accompanying teachers) and school personnel in foundation training and related agencies, (2) providing opportunities for teachers to develop learning methods in the classroom, (3) observing or supervising classroom teaching, (4) evaluating teacher performance, and (5) giving awards or giving awards to teachers and staff.